갈륨이 첨가된 산화아연막의 코팅에 따른 미세팁 구조 탄소나노튜브의 전계방출 특성 및 장시간 안정성 - 김종필; 노영록; 조경철; 이상렬; 박진석 (한국반도체디스플레이기술학회, 2009)
Carbon nanotubes (CNTs) were coated with undoped zinc oxide (ZnO) or 5 wt% gallium-incorporated ZnO (GZO) using various deposition conditions. The CNTs were directly grown on conical-type tungsten substrates at 700 °C using inductively coupled plasma-chemical vapor deposition. The pulsed laser deposition technique was used to deposit the ZnO and GZO thin films with very low stress. Field-emission scanning electron microscopy and high-resolution transmission electron microscopy were used to monitor the variations in the morphology and microstructure of CNTs prior to and after ZnO or GZO coating. The formation of ZnO and GZO films on CNTs was confirmed using energy-dispersive x-ray spectroscopy. In comparison to the as-grown (uncoated) CNT emitter, the CNT emitter that was coated with a thin (10 nm) GZO film showed remarkably improved field emission characteristics, such as the emission current of 325 μA at 1 kV and the threshold field of 1.96 V/μm at 0.1 μA, and it also exhibited the highly stable operation of emission current up to 40 h.